De funkar grymt bra möblerna ;) : Uppföljning av ett mobilt lärandeprojekt i gymnasieskolan - Ekberg, Niclas (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2013)
In 2011, a mobile learning project, mLearning, was initiated among students and staff in two upper secondary school classes in northern Sweden. The project's objectives were to help students and staff coordinate their planning, communicate and exchange information, support students' digital competence development, find new ways of expression and create better opportunities for students to learn and for teachers to teach. The purpose of the report was to help create knowledge about how smartphones are used within the framework of a school-related project at the upper secondary school level, and to understand what the project phone and its use means to students and teachers. The report also tried to evaluate the extent to which the mobile learning project met its objectives. The investigation was mainly based on an individual web survey consisting of both quantifiable and open questions. The supporting data also consisted of group interviews with participants and the participants' individual monthly reports regarding their phone use. The hermeneutical processing of the data resulted in three themes. The first theme, "The easy management of information", was derived from the experiences of the ease and speed with which the ever-present mobile phone enables information searches and fact checks. The second theme, "The strengthened communication", primarily focused on strengthened communication but, to some extent, also focused on strengthened relationships, both between teachers and students and between students themselves. The third theme, "The far from obvious meaning of the project mobile", focused on the widely experienced feeling of independence in relation to the technology and the opportunity to personally shape the use of technology. Here, tendencies for marginalisation and a lack of influence regarding the technology and its use were also noted. The results showed that the mobile learning project met its objectives when it came to helping students and staff coordinate their planning, communicate and exchange ...